Трематоды (Trematoda, Monorchiidae) ночниц Myotis brandtii и M. mystacinus (Chiroptera, Vespertilionidae) Самарской Луки (Россия) - Демидова, Т.Н.; Вехник, В.П. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2004)
Проанализированы материалы по трематодам видов-двойников Myotis brandtii (Eversmann, 1845) и Myotis mystacinus (Kuhl, 1819). Всего обнаружено 9 видов трематод — Plagiorchis elegans, P. koreanus, P. muelleri, P. vespertilionis, Lecithodendrium linstowi, Prosthodendrium ascidia, P. chilostomum, P. longiforme, Parabascus duboisi. Отмечены некоторые особенности морфологии и экологии паразитов. Выявлены различия трематодофаун двух видов рукокрылых — у M. brandtii отмечены все 9 видов трематод, у M. mystacinus — лишь Plagiorchis koreanus и Prosthodendrium ascidia. Data on trematodes of two sibling species Myotis brandtii (Eversman, 1845) and Myotis mystacinus (Kuhl, 1819) are analyzed. 9 trematodes species were found — Plagiorchis elegans, P. koreanus, P. muelleri, P. vespertilionis, Lecithodendrium linstowi, Prosthodendrium ascidia, P. chilostomum, P. longiforme, Parabascus duboisi. Some morphological and ecological characteristics of parasites are discussed. Differences between tematodes fauna of sibling species were detected: M. brandtii infected by 9 trematode species, but M. mystacinus infected just by 2 species — Plagiorchis koreanus и Prosthodendrium ascidia.